Ecotourism hubs as an articulator of sustainable urban landscape in Morales–San Antonio - Miguel Mesias, Leon Ruiz; Nahún, Gil Gonzales; Estaylor Marcelino, Vilchez Ramos; Luisa Enith, Chafloque Pinedo (Frontiers in Built Environment, 2024)
The San Martín region, located in the Peruvian jungle, presents ecological constraints regarding environmental tourism, encompassing natural and cultural resources. However, unplanned urban growth is degrading the urban landscape, with the town center of San Antonio being the most affected, losing approximately 377 ha. in natural forest. Therefore, this research presents the following question: How do ecological tourism hubs articulate the sustainable urban landscape of the Morales–San Antonio axis? The objectives of this research are to identify centers of ecological tourism, delimit perimeters and geomorphological patterns, interpret the territory and its transition through landscape transformations, and recognize the social tourism dynamics of people in the province. Likewise, this research has a qualitative approach, whose instruments were the observation sheet, open interview, and municipal documents, and the data collection techniques were through satellite images, cartography, photographic records, and design software. The result is evidence of an axis with tourism potential in the city of Tarapoto, which is experiencing very accelerated urban growth and where urbanized ecological places can be seen. Indicators were also identified for tourism centers organized into four groups: buildings with tourism potential, natural remnants, ecological areas, and permanently flooded and/or swampy areas. Finally, it is concluded that the city of Tarapoto has ecological tourism centers and that these are articulated in the sustainable urban landscape of the Morales–San Antonio axis.